Incidence, mortality, and global burden of retinoblastoma in 204 countries worldwide from 1990 to 2021: Data and systematic analysis from the Global Burden of Disease Study 2021 - Linyan Wang; Jianing Chen; Yunhan Shen; Grace Loy Ming Hooi; Shuohan Wu; Feng Xu; Hao Pei; Jianpeng Sheng; Tiansheng Zhu; Juan Ye (Neoplasia: An International Journal for Oncology Research)
Background: Retinoblastoma (Rb), the primary intraocular malignancy in children, poses significant risks, yet its overall burden remains inadequately assessed. This study aims to analyze global Rb trends using Global Burden of Disease, Injuries, and Risk Factors study (GBD) 2021 data. Methods: GBD 2021 data was analyzed to assess Rb incidence, mortality, and disability-adjusted life years (DALYs) from 1990 to 2021. Average annual percentage changes (AAPCs) were calculated across genders, age groups (0-9 years), and geographic regions categorized by socio-demographic index (SDI) quintiles. Results: From 1990 to 2021, the global Rb age-standardized incidence rate (ASIR) increased from 0.08 (per 100,000, range: 0.05 to 0.10) to 0.09 (per 100,000, range: 0.06 to 0.13). ASIR was not significantly correlated with SDI (R = -0.095, P = 0.18), while age-standardized DALYs rate (R = -0.693, P < 0.001) and age-standardized mortality rate (ASMR) (R = -0.71, P < 0.001) were significantly and negatively correlated with SDI. Increases in ASIR were concentrated in Asia, Europe, and northern and southern Africa. The highest standardized DALYs and ASMR were noted in certain countries in Asia, Europe, and South Africa. Among age groups, the highest disease burdens were observed in the “0-6 days” and “2-4 years” groups. There were no significant gender differences in Rb burden globally. Conclusions: Despite global progress, regions with lower SDI face elevated Rb burden and mortality. Females exhibit higher burdens during infancy, necessitating further investigation. Effective Rb management in resource-limited areas requires international collaboration focused on health education, early diagnosis, and prenatal screening for high-risk families.